2017
DOI: 10.1038/ncomms14932
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycle peptides delineate locked-open inhibition mechanism for microorganism phosphoglycerate mutases

Abstract: Glycolytic interconversion of phosphoglycerate isomers is catalysed in numerous pathogenic microorganisms by a cofactor-independent mutase (iPGM) structurally distinct from the mammalian cofactor-dependent (dPGM) isozyme. The iPGM active site dynamically assembles through substrate-triggered movement of phosphatase and transferase domains creating a solvent inaccessible cavity. Here we identify alternate ligand binding regions using nematode iPGM to select and enrich lariat-like ligands from an mRNA-display ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 59 publications
2
80
0
Order By: Relevance
“…We also solved the tertiary structures of some of the above thioether macrocyclic peptides by X‐ray crystallographic analyses (Figure A‐F). It is quite remarkable that we have witnessed a wide range of tertiary structures, eg, a ®‐sheet structure (PlexB1, Figure A; and KDM4A, Fig B), a macrocyclic structure containing an α‐helix motif (CmABCB1, Figure C), a macrocyclic structure containing a water molecule in the ring (SIRT2, Figure D), and a compact macrocyclic structure with a tail linear peptide (human α‐amylase; MATE, Figure E; iPGM, Figure F). The above results indicate how the RaPID system effectively samples a wide range of tertiary structures of macrocyclic peptides from the libraries.…”
Section: Rapid System An Enabling Technology That Rapidly Discovers mentioning
confidence: 99%
See 2 more Smart Citations
“…We also solved the tertiary structures of some of the above thioether macrocyclic peptides by X‐ray crystallographic analyses (Figure A‐F). It is quite remarkable that we have witnessed a wide range of tertiary structures, eg, a ®‐sheet structure (PlexB1, Figure A; and KDM4A, Fig B), a macrocyclic structure containing an α‐helix motif (CmABCB1, Figure C), a macrocyclic structure containing a water molecule in the ring (SIRT2, Figure D), and a compact macrocyclic structure with a tail linear peptide (human α‐amylase; MATE, Figure E; iPGM, Figure F). The above results indicate how the RaPID system effectively samples a wide range of tertiary structures of macrocyclic peptides from the libraries.…”
Section: Rapid System An Enabling Technology That Rapidly Discovers mentioning
confidence: 99%
“…We also found antagonists against human intracellular enzymes, a ubiquitin ligase (E6AP), a kinase (AKT2), and histone deacetylase and demethylase (SIRT2 and KDM4A). We recently reported antagonists against a pathogenic microorganism enzyme, a cofactor‐independent phosphoglycerate mutase (iPGM), and an inhibitor against Zaire Ebola virus protein 24 (VP24) disrupting the protein‐protein interaction with and human karyopherin alpha 5‐KPNA5 . Moreover, thioether‐macrocyclic peptides against a cancer stem cell marker, EpCAM were reported to devise a potential imaging probe .…”
Section: Rapid System An Enabling Technology That Rapidly Discovers mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such display platforms have been used to isolate macrocyclic peptide ligands against diverse protein targets, including enzymes, proteases, cellular receptors, and growth factors [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…7 When an mRNA template is tethered with a puromycin at the 3 0 end, puromycin leads to the covalent ligation of mRNA and its encoded peptide so that the mRNA-puromycin-peptide complex is released as a translation product. 9 Crystallographic analysis of the selected macrocyclic peptide-iPGM complex revealed that the peptide ligand was cradled in a pocket at the bi-domain interface, slightly shifted from the substrate binding site (Figure 2(b)). After a number of cycles, enriched peptide "hits" with high target affinity are sorted out and characterized by DNA sequencing (Figure 2(a)).…”
mentioning
confidence: 99%